'Nothing about us without us': the emerging disability movement and advocacy in China. Issue 7 (9th August 2017) - Zhang, Chao
Abstract: The disability movement and disabled persons' self-help organizations (DPOs) are emerging in China, some of which succeeded in promoting policy and social changes with special strategies. Based on an original survey and interview, this article explains the development and survival strategies of China's DPOs, and especially interprets some successful cases of social advocacy and policy advocacy in the emerging disability movement. It is hoped that scholars will pay more attention to the advocacy and public engagement of the disability community in non-western settings in the future.